EFEITO BIOLÓGICO DO EXTRATO DE FOLHAS DE OLIVEIRA (OLEA EUROPAEA L.) EM RATOS SUBMETIDOS À DIETA HIPERLIPÍDICA - Bruna da Fonseca Antunes; Cristielle Aguzzi Cougo De Leon; Alexandre Lorini; Camila Castencio Nogueira; Elizabete Helbig; Rui Carlos Zambiazi (Universidade do Estado do Rio de Janeiro, 2018)
Objective: In order to explore the nutritional and bioactive characteristics of the olive leaf, the study aimed to evaluate the biological potential of olive leaves by analyzing the effect of leaf extract on the glycemic and lipid profile of Wistar rats subjected to a hyperlipidic diet . Methodology: The experiment lasted 70 days; animals were divided and randomly distributed into 4 groups of 6 rats each, being N: normocaloric diet + water; H: hyperlipidic diet + water; NE: normocaloric diet + extract; and HE: hyperlipidic diet + extract. At the end of the experiment the effect of the aqueous extract of olive leaves on glycemia, lipid profile and lipid peroxidation were determined in rats. Results: The consumption of olive leaf extract by rats promoted changes in lipid profile and beneficial effect on the thiobarbituric acid reactive substances (TBARS) levels. Conclusions: Due to their  chemical composition,  rich in nutrients and compounds with bioactive properties, in addition to its considerable antioxidant and biological activities, olive leaves can be an option as a food supplement with biological properties. DOI: 10.12957/demetra.2018.37273